KEKUATAN MISTISISME AGAMA DALAM PROSES KEBANGKITAN MANUSIA PASCA BENCANA ALAM: RESPON WARGA MUHAMMADIYAH KOTA PADANG - Riki Saputra (Menara Ilmu, 2018)
The dimension of religion can not be separated from the events of natural disasters.Placing the approach of religious mysticism as one of the most important approaches indisaster recovery process. Research focusing on the actions of religious groups ondisasters or disaster victims is minimal. Religious groups are an important part inassisting the recovery of victims of natural disasters, especially in Padang. One moderateIslamic group like Muhammadiyah has provided significant relief assistance in Padang.Religion provides and teaches messages that can make people or disaster victims feelstrong and accept disaster as part of their life processes in the world. Informants in thisstudy are Muhammadiyah residents spread across several districts. Data collection in thestudy using interviews and documentation.Keywords: Religious Mysticism, Muhammadiyah, Disaster